PERCEPTIONS AND EXPERIENCES OF MOTHERS WITH A HISTORY OF EPISIOTOMY ON BARRIERS AND SOCIAL SUPPORT IN BREASTFEEDING - Hidayah, Lisnah; Mahendra Tri Arif Sampurna; Farida Fitriana; Euvanggelia Dwilda Ferdinandus; Maria Ulfa (Indonesian Midwifery and Health Sciences Journal, 2024)
Abstract Background: Breastfeeding rates in Indonesia have decreased significantly in recent years. In 2021, less than half of babies in Indonesia (48.6 percent) were breastfed in the first hour of life, down from 58.2 percent in 2018. Only 52.5 percent were exclusively breastfed in the first six months, which is a decrease sharply from 64.5 percent in 2018. The success of breastfeeding is determined by several inhibiting and supporting factors, one of which is anxiety due to an episiotomy. Episiotomy is often performed to prevent more severe perineal tearing during labor, but there is controversy regarding the benefits and risks of episiotomy, as well as its impact on breastfeeding practices. Objective: To describe the perceptions and experiences of mothers with a history of episiotomy regarding barriers and support in providing breast milk at 7 days postpartum at Airlangga University Hospital, Surabaya City. Method: This research was conducted using qualitative methods with a phenomenological approach/Interpretive Phenomelogical Analysis (IPA). The method for taking subjects used purposive sampling. This research involved a total of 8 informants. The analysis method used is content analysis. Results: It was found that the perception of mothers with a history of episiotomy regarding breastfeeding and their intention to breastfeed was still low. The experience of providing breast milk varies greatly and mothers tend to be physically and emotionally uncomfortable. Social support is very important for mothers' behavior in providing breast milk. There are physical and psychological barriers associated with episiotomy including pain, physical discomfort, anxiety about health and recovery so that breastfeeding behavior becomes disrupted.